Socialization of the Role of the Family in the Participation of Beginner Voters in the 2024 Election in Muara Badak Ilir Village, Muara Badak District, Kutai Kartanegara Regency - Eryani, Trisna Waty Riza; Putri, Aisyah (PT FORMOSA CENDEKIA GLOBAL, 2024)
Political participation is an important aspect in the democratic process, political participation from first-time voters is one form of implementing a democratic system that is running well. In general, if the level of public participation in the democratic process is greater, it is considered good, conversely, if the level of public participation is low, it is generally considered less good, because it can mean that many citizens are indifferent to elections. Especially for first-time voters who have voting rights but cannot use them properly. Most of these new voters are still unstable, can't decide, or don't even care about the election at all. This is the role of the family, especially parents, in providing knowledge about the importance of participating in elections. The aim of community service is to socialize the role of the family in the participation of first-time voters in the 2024 elections. The method of community service is lectures and discussions. The results of the socialization activities went well, and there were 10 participants consisting of parents in Muara Badak Ilir Village, Muara Badak District. Parents who have teenage children are very enthusiastic about taking part in this activity because it can increase knowledge about political participation for novice voters, namely their children.